Developing a Taxonomy, Root-Cause Analysis, and Adaptive Remediation Framework for JVM Garbage Collection (GC) Overhead Errors in Apache Spark under High-Scale Commerce Workloads - Vamsidhara Reddy Doragacharla (International Journal of Intelligent Systems and Applications in Engineering, 2025)
The study examines the JVM GC overhead error in Apache Spark with the close-out of a commerce-scale load and suggests an overview, cause and effect examination, and enhanced adaptive remedies. The framework employs Python software to analyze performance in real-time and make dynamic JVM configuration changes. The experimental outcomes of the suggested scheme prove that the proposed framework minimizes GC delays and job times, increasing throughput and system efficiency astonishingly. The research not only contributes to the performance optimization of Apache Spark in the large litter setting, but also provides insights into the automation of JVM settings to reduce overhead. DOI: https://doi.org/10.17762/ijisae.v13i2s.8195